Home blood pressure measurement for hypertension management in the real world: Do not just measure, but share with your physician - Rhee, Moo-Yong; Munakata, Masanori; Nah, Deuk-Young; Kim, Je Sang; Kim, Hae-Young (Frontiers in Cardiovascular Medicine, 2023)
Background: Studies of the effectiveness of home blood pressure (BP) measurement on the treatment of hypertension in the real world are sparse, and the results are controversial. There is an efficacy-effectiveness gap in the treatment of hypertension using home BP measurements. We aimed to investigate the effect of reporting home BP to physicians on ambulatory BP control as a factor contributing to the efficacy-effectiveness gap in treating patients with hypertension. Methods: We recruited patients ≥20 years of age taking antihypertensive drugs. Office and 24-hour ambulatory BP were measured. A questionnaire to the measurement of home BP was administered. Participants were divided into an HBPM(-) group, home BP was not measured (n=467); HBPM(+)-R(-) group, home BP was measured but not reported (n=81); and HBPM(+)-R(+) group, home BP was measured and reported (n=125). Results: The HBPM(+)-R(+) group had significantly lower office systolic BP (SBP, p=0.035), 24-hour SBP (p=0.009), and daytime SBP (p=0.016) than the HBPM(-) group, and lower nighttime SBP (p=0.005) and diastolic BP (DBP, p=0.008) than the HBPM(+)-R(-) group. In the multivariate analysis, the differences in 24-hour SBP, daytime SBP, and nighttime DBP remained significant. There was a significant difference between groups in the control rate of 24-hour SBP (p=0.046), nighttime SBP (p=0.021), and nighttime DBP (p=0.023). The nighttime SBP and DBP control rates in the HBPM(+)-R(+) group were higher than those in the HBPM(+)-R(-) group (p=0.006 and 0.010, respectively). Among patients measuring home BP, the adjusted odds ratio for 24-hour and nighttime BP control in the HBPM(+)-R(+) group were 2.233 and 3.658, respectively. Conclusion: Home BP measurement should be reported to the treating physician to effectively manage hypertension.